Customer Data Platforms Use People Data to Transform the Future of Marketing Engagement. - Kihn, Martin (John Wiley & Sons, Incorporated, 2020)
The Customer Data Problem -- CHAPTER 2 The Brief, Wondrous Life of Customer Data Management -- Customer Data on Cards and Tape? -- Direct Mail and Email: The Prototypes of Modern Marketing -- A Brief History of Customer Data Management -- Relational Databases -- The Rise of CRM and Marketing Automation -- Marketing Automation -- Improved User Interface (UI) -- The Multichannel Multiverse of the Thoroughly Modern Marketer -- The Growth of Digital -- Today's Landscape -- Today's Martech Frankenstack -- Customer-Driven Thinker: Scott Brinker.